The best of I-Witness, volume 4 - GMA News and Public Affairs (Quezon City GMA Network, 2009)
Collection of best episodes of I witness, a documentary television show in the Philippines by GMA Network. This volume describes the life of different people such as former chain smokers who sound like robots after their cancerous vocal chords are surgically removed, a group of beggars who rely on feeding programs for their survival, children of Magalumbi Island who swim 2 kilometers through the open sea just to get to school, and children who are pregnant and children who already bore a child at their young age.
Boses upos (29 min., 32 sec.) -- Papa, papa, paano ako ginawa (31 min., 10 sec.) / Howie Severino -- Biyaheng sikmura (28 min., 23 sec.) -- Promdi city (27 min., 27 sec.) / Kara David -- Batang kalabaw (26 min.) -- Batang langoy (25 min., 20 sec.) / Jay Taruc -- Iskul ko no. 1 (31 min., 32 sec.) -- Nanay na si Nene (30 min., 32 sec.) / Sandra Aguinaldo.
Hosts, Jose Reyes Taruc, Kara S. David, Sandra S. Aguinaldo, Horacio Severino
DVD.
Keywords: Nonfiction television programs; Documentary television programs; Teenage mothers -- Philippines; Poverty -- Philippines; Social problems -- Philippines